A Juridical Analysis of Death Penalty for Narcotics Abuse - Paras Setio (Jurnal Hukum Novelty, 2018)
Narcotics abuse is currently one of the biggest problems in Indonesia. The dangers posed by Narcotics Abuse have harmed the nation’s young generation, therefore the Government continues to strengthen law enforcement regarding the issue of Narcotics abuse. The usage of narcotics is currently regulated in acts number 35 of 2009. In the acts, the government implements maximum sanction in the form of death penalty to certain categories of narcotics abuse. Until 2016, there were 55 perpetrators of narcotics related crimes who had been sentenced to death by Indonesian courts. This research aims to explore the judges’ considerations as well as the obstacles they face in implementing death penalty to narcotics abusers. This research was conducted in the District Court of Magetan. Data was collected from primary and secondary data sources in the form of library studies and field studies. The sampling method used was purposive sampling to determine a judge of the District Court of Magetan who had sentenced narcotic abusers to death as the respondent. Furthermore, the approach of this research is sociological juridical approach. The collected data were analysed using qualitative descriptive method. This study reveals that the judges based their decision to pass death sentence on the act No 35 of 2009. In addition, the judge also took several juridical factors and sociological facts into considerations. The judge did not find any obstacles in passing death penalty because the case examiners agreed to impose death penalty.